Estimation of Native Nutrient Supplying Capacity of Soil for Improving Wheat (Triticum Asestivum L.) Productivity in Chitwan Valley, Nepal - Adhikari, A.R.; Adhikari, K. R.; Regmi, A.P.; McDonald, A. (International Journal of Applied Sciences and Biotechnology, 2014)
Three field experiments were conducted at farmer's field of Torikhet, Gopaljung and Kalyanpur of Chitwan Valley, Nepal during Nov 2011- April 2012 to assess N, P and K supplying capacity of soil. Each experimental site consists of four replications and five treatments laid out in RCB design. Among the five treatments, -N, -P and -K were set to estimate the inherent N, P and K supplying capacity of soil respectively. Highest uptake of N (100 Kg ha-1), P (21 Kg ha-1) and K (84 Kg ha-1) by wheat and highest native N (41 Kg ha-1), P (18 Kg ha-1) and K (72 Kg ha-1) supplying capacity of soil was recorded at Kalyanpur. Similarly, N, P and K required to produce one Mg of wheat grain was found highest in Kalyanpur. Based on the yield obtained in fully fertilized plot, target yield of 5 Mg ha-1 was set. Finally, N, P and K fertilizer needed were calculated on the basis of nutrient required for target yield, NPK supplying capacity of soil and recovery efficiency of NPK from fully fertilized plot. To obtain the target grain yield of 5 Mg ha-1, N: P: K at differential rate of 140: 30.5: 57 Kg ha-1, 140:27:53 Kg ha-1 and 120:22.5:38.5 Kg ha-1 has to be supplied from external source in Torikhet, Gopaljung and Kalyanpur respectively. This research outcome strengthens the fact that spatial variability for soil nutrient supplying exist across the farmer’s field. So it is necessary to estimate that variability for improving wheat productivity. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11276 Int J Appl Sci Biotechnol, Vol. 2(4): 478-482